2004
DOI: 10.1108/03090590410542693
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of training and remuneration in the accommodation industry

Abstract: It has long been recognised that effective staff training and remuneration allows an organisation to provide a unique and differentiating standard of service in industry, resulting in increased profitability to service providers. The purpose of this research study is to investigate the training strategies, and hence the training profile, of organisations within the accommodation sector. The extent and role of training and remuneration is examined in local independent accommodation providers, and then compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Companies expect to increase service and product quality and innovative activities and also productivity due to faster adaptation of employees to new conditions, as a result of investment in employee training (Dearden et al, 2006;González et al, 2016;Mathews, 2002;Taylor & Davies, 2004). The fact that the structure of organizations has become more complex over time and the need for new skills due to the expansion of the job descriptions of employees has made the provision of employee training widespread (Knoke & Yang, 2003).…”
Section: Challenges In Employee Trainingmentioning
confidence: 99%
“…Companies expect to increase service and product quality and innovative activities and also productivity due to faster adaptation of employees to new conditions, as a result of investment in employee training (Dearden et al, 2006;González et al, 2016;Mathews, 2002;Taylor & Davies, 2004). The fact that the structure of organizations has become more complex over time and the need for new skills due to the expansion of the job descriptions of employees has made the provision of employee training widespread (Knoke & Yang, 2003).…”
Section: Challenges In Employee Trainingmentioning
confidence: 99%
“…A study by Tukunimulongo ( 2016) found that training-on-the job helps the employee to relate the job in the course of learning; which Taylor and Davis (2004) advances that it is a better method for firms to save on time and cost. Shafini et al(2016) in their study argued that off-the-job training is the most effective training and development approach to enable employees increase their productivity and meet increased demands of customers and in turn help the firm make more profits.…”
Section: Employee Strategic Trainingmentioning
confidence: 99%
“…Management can use uniforms as visual symbols to continuously transfer firm values to and among their employees [26,27] and uniforms have communicative power in both, the external and internal spheres of a corporation. Furthermore, for many hotel organizations, uniforms have been part of an employee benefit package for some time now and therefore can contribute to staff satisfaction and commitment [11,12]. In summary, uniform features in the service industries include attributes such as functionality, comfort, materials, appropriateness to job task, style, colour and overall fit [13].…”
Section: Uniform Featuresmentioning
confidence: 99%
“…Furthermore, for many hotel organizations, uniforms are part of employee benefit packages and therefore can contribute to work commitment, organizational identification, and higher staff satisfaction [11][12][13].…”
Section: Introductionmentioning
confidence: 99%